2011
DOI: 10.1111/j.1365-2605.2010.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paternal diet‐induced obesity on sperm function and fertilization in a mouse model

Abstract: Although obvious effects of obesity on female reproduction and oocytes are emerging, the effects on male fertility and sperm quality are less clear with studies reporting conflicting results. We hypothesize that male obesity affects sperm function and physiology probably as a result of elevated oxidative stress in spermatozoa and therefore elevated levels of sperm DNA damage and loss of function. Six-week-old C57/Bl6 male mice (n = 36) were randomly allocated to two groups: group 1 (n = 18) received a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
210
8
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(255 citation statements)
references
References 48 publications
26
210
8
11
Order By: Relevance
“…The model of paternal diet induced obesity used here recapitulated that sperm from males fed a HFD had reduced motility and increased levels of intracellular ROS, compared to sperm from CD fed males. This is consistent with previous studies in similar models that demonstrate that not only does HFD feeding result in an obese phenotype [9, 11, 12, 14-16, 32, 36-38] but also correlates with impaired sperm quality [15,16,[36][37][38]. Although testosterone concentrations were not measured in these HFD fed males, we speculate that their observed subfertility may be associated with lowered testosterone concentrations, as previously demonstrated [36,37].…”
Section: Discussionsupporting
confidence: 79%
“…The model of paternal diet induced obesity used here recapitulated that sperm from males fed a HFD had reduced motility and increased levels of intracellular ROS, compared to sperm from CD fed males. This is consistent with previous studies in similar models that demonstrate that not only does HFD feeding result in an obese phenotype [9, 11, 12, 14-16, 32, 36-38] but also correlates with impaired sperm quality [15,16,[36][37][38]. Although testosterone concentrations were not measured in these HFD fed males, we speculate that their observed subfertility may be associated with lowered testosterone concentrations, as previously demonstrated [36,37].…”
Section: Discussionsupporting
confidence: 79%
“…Studies on obese men (Kort et al 2006, Chavarro et al 2009 showed increased numbers of sperm with DNA fragmentation, findings that are partly corroborated by animal studies that have shown a small increase in sperm with nDNA damage (Bakos et al 2011) and evidence of one of its consequences, decreased implantations (Ghanayem et al 2010). This contrasts with the findings of our study, that showed no difference in the sperm nDNA status of either animal model.…”
Section: Discussioncontrasting
confidence: 57%
“…27 Some components of high-energy diets, such as trans fatty acids and saturated fats, have the potential to adversely affect the testicular lipid metabolism and impair sperm production. In another animal study, Bakos et al 40 reported that paternal-diet-induced obesity decreased both the motility and the fertilizing ability of sperm in male mice. Morgan et al 34 also reported that elevated levels of plasma cholesterol induced by a cholesterol-rich diet negatively affected spermatogenesis in rabbits.…”
Section: Introductionmentioning
confidence: 99%